2023
DOI: 10.1021/acsomega.3c02082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Drug Simulation and Experimental Validation of the CD36 Receptor Competitively Binding to Long-Chain Fatty Acids by 7-Ketocholesteryl-9-carboxynonanoate

Abstract: Long-chain fatty acids (LCFAs) are one of the main energy-supplying substances in the body. LCFAs with different lengths and saturations may have contrasting biological effects that exacerbate or alleviate progress against a variety of systemic disorders of lipid metabolism in organisms. Nonalcoholic fatty liver disease is characterized by chronic inflammation and steatosis, mainly caused by the ectopic accumulation of lipids in the liver, especially LCFAs. CD36 is a scavenger receptor that recognizes and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…The ACSL1 has been found to play key roles in the regulation of triglyceride synthesis by activating fatty acid, i.e., altering the free LCFAs to fatty acyl-CoA esters [ 28 ]. CD36 , also known as the scavenger receptor B2, is a key fatty acid sensor and regulator of lipid metabolism, which has a high affinity for long-chain fatty acids and can bind and transport them into cells [ 27 , 29 , 30 ]. Reports have found that the expression of CD36 was significantly increased in the lactation of cows, and the overexpression of CD36 increased the uptake of LCFAs in the mammary cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ACSL1 has been found to play key roles in the regulation of triglyceride synthesis by activating fatty acid, i.e., altering the free LCFAs to fatty acyl-CoA esters [ 28 ]. CD36 , also known as the scavenger receptor B2, is a key fatty acid sensor and regulator of lipid metabolism, which has a high affinity for long-chain fatty acids and can bind and transport them into cells [ 27 , 29 , 30 ]. Reports have found that the expression of CD36 was significantly increased in the lactation of cows, and the overexpression of CD36 increased the uptake of LCFAs in the mammary cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if the simulation lacks crucial real-world data on external environmental factors or unexpected biological responses, the predictions may deviate significantly from the actual outcomes. These models, while sophisticated, often require experimental validation to ascertain their predictions [ 9 , 10 ]. In conclusion, CADD signifies the harmonious blend of biology and technology, aiming to expedite drug discovery.…”
Section: Introduction To Computer-aided Drug Design (Cadd)mentioning
confidence: 99%